1998
DOI: 10.1212/wnl.50.2.388
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein E and alpha‐1 antichymotrypsin polymorphism genotyping in Alzheimer's disease and in dementia with Lewy bodies Distinctions between diseases

Abstract: The possibility of gene interactions in Alzheimer's disease (AD) has been suggested by the finding of an association of the AA genotype of the alpha-1 antichymotrypsin (AACT) gene and the apolipoprotein E (apoE) epsilon 4/4 genotype in AD. We tested this possibility by genotyping a large series of clinically and neuropathologically confirmed cases of AD and a series of cases with dementia with Lewy bodies (DLB) with a matched control group for the AACT locus and apoE. ApoE genotyping showed the established fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 2 publications
1
20
0
Order By: Relevance
“…Although this association was con®rmed in a group of Japanese AD patients [Yoshiiwa et al, 1997], several other groups have not found this association in Caucasian AD patients Muller et al, 1996;Nacmias et al, 1996;Talbot et al, 1996;Didierjean et al, 1997;Helisalmi et al, 1997;Morgan et al, 1997;Murphy et al, 1997;Lamb et al, 1998]. Also, Muramatsu et al [1996] found a nonsigni®cant trend for the AA genotype in Japanese AD patients, which was signi®cant only in non-E4 individuals.…”
Section: Discussionmentioning
confidence: 94%
“…Although this association was con®rmed in a group of Japanese AD patients [Yoshiiwa et al, 1997], several other groups have not found this association in Caucasian AD patients Muller et al, 1996;Nacmias et al, 1996;Talbot et al, 1996;Didierjean et al, 1997;Helisalmi et al, 1997;Morgan et al, 1997;Murphy et al, 1997;Lamb et al, 1998]. Also, Muramatsu et al [1996] found a nonsigni®cant trend for the AA genotype in Japanese AD patients, which was signi®cant only in non-E4 individuals.…”
Section: Discussionmentioning
confidence: 94%
“…Kamboh et al [83] genotyped subjects at a di-allelic polymorphism in a region of the ACT gene coding for either threonine (T allele) or alanine (A allele); they found that the combination of the ACT/AA genotype and the APOE Â4 allele increased the risk of late-onset AD 2-to 3-fold. Subsequent reports did not support this effect of the ACT polymorphism alone or in combination with the APOE Â4 allele [84].…”
Section: Bleomycin Hydrolasementioning
confidence: 94%
“…PCR amplification of the two polymorphic sites which determine APO E Â genotype (codons 112 and 158) was performed using oligonucleotide primers; forward 5)-TCCAAGGAGCTGCAGGCGG-CGCA-3) and reverse 5)-ACAGAATTCGCCCCGGCCTGGTA-CACTGCCA-3) using previously described methods [22,28,29].…”
Section: Apo E Genotypingmentioning
confidence: 99%
“…Tissue blocks from the formalin-fixed right hemisphere were taken from the frontal, temporal, occipital and parietal cortex, embedded in paraffin wax and sections were cut at 10 Ìm thickness on a microtome [22]. Routine histology was carried out on the four cortical regions and SP and NFT were stained with Von Braunmühl's method and Palmgren's silver method [30], respectively, for AD diagnosis and quantification of SP and NFT.…”
Section: Neuropathological Examinationmentioning
confidence: 99%
See 1 more Smart Citation